Synthesis of New Single CFOA-Based VCOs Incorporating the Voltage Summing Property of Analog Multipliers. (18th September 2012) - Gupta, S. S.; Bhaskar, D. R.; Senani, R.
Abstract : Recently, current feedback operational amplifier (CFOA) and analog multiplier-(AM-) based-voltage controlled oscillators (VCOs) have been published in the literature which require 2 CFOAs and 2 AMs for linear tuning law between control voltage and frequency of oscillation. In this paper, a family of eight new voltage-controlled oscillators (VCOs), with linear tuning laws, employing only a single CFOA in conjunction with two analog multipliers (AMs), has been derived through a systematic state-variable methodology. This has been made possible by exploiting the voltage summing property of the multiplier chosen which has never been done in the literature earlier. The workability of the presented VCOs has been verified by experimental results based on AD844 type CFOAs and AD534 type AMs, and the advantages of new circuits over the previously known CFOA-AM-based VCOs have been highlighted.